Método de análise da aplicação da mistura asfáltica tipo SMA com enfase no parâmetro pneu-pavimento - estudo de caso na avenida do Contorno em Belo Horizonte/MG Brasil Contorno em Belo Horizonte/MG Brasil - Bernardo de Brito Pereira (2024)
Tire-pavement adhesion is a parameter of great importance for evaluating the surface behavior of the asphalt coating. The present work correlated the macrotexture and microtexture parameters of the SMA (Stone Matrix Asphalt) coating obtained from the sand stain and British pendulum tests carried out on Avenida do Contorno in Belo Horizonte. Data on traffic accidents that occurred before and after the execution of the SMA-type asphalt coating, and the trend of accident occurrences were also analyzed using a linear regression graph. To complement this, a qualitative and quantitative questionnaire was applied to BHTRANS bus drivers. The ADSR (Action Design Science Research) method applied in the research provided the integration of the desired objectives, in order to identify perceptions of improvement in road safety in the study section. In the correlation analysis using the Pearson method between the macrotexture and microtexture variables, a low intensity and positive relationship was identified, corroborating research published in academia. Subsequently, it was found that the annual average of traffic accidents was 36% lower after the implementation of the SMA coating, meanwhile, the number of motor vehicles in the city of Belo Horizonte grew by approximately 81% between the years 2011 and 2022. When developing the linear regression graph, it was identified that the expectation of traffic accidents is falling over the years, and in 2025 the expectation of accidents is 50% lower compared to the pre-SMA coating period. In the artifact evolution stage, the questionnaire applied demonstrated that 89% of the drivers interviewed stated that the application of SMA brought safety gains when driving the vehicle in dry periods and especially on rainy days. It is understood that the use of the research artifact was effective, as it presented satisfactory and constructive results regarding the benefits of using asphalt coatings that promote greater adhesion between tire and pavement.